2020
DOI: 10.3390/ani10040653
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification Using Soy Lecithin and Sucrose: A New Way to Store the Sperm for the Preservation of Canine Reproductive Function

Abstract: Simple Summary: Soy lecithin and sucrose were used at different concentrations to develop and compare different vitrification methods for the cryopreservation of canine semen. All of the sperm quality characteristics were effectively preserved after devitrification when vitrification extenders containing soy lecithin at 1% and 0.25 M sucrose were used. The results suggest that vitrification is effective, fast, and simple for cryopreservation of canine semen. Furthermore, the use of soy lecithin in lieu of anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
3
9
1
2
Order By: Relevance
“…According to these two experiments, the quality of the sperm after thawing was comparable to that after freezing in a Tris egg yolk (TEY) extender. Axnér & Lagerson, (2016) and Pipan et al, (2020) concluded that for freezing dog semen, an extender with 1% soybean lecithin extender produced superior post-thaw sperm motility than 2% soybean lecithin.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these two experiments, the quality of the sperm after thawing was comparable to that after freezing in a Tris egg yolk (TEY) extender. Axnér & Lagerson, (2016) and Pipan et al, (2020) concluded that for freezing dog semen, an extender with 1% soybean lecithin extender produced superior post-thaw sperm motility than 2% soybean lecithin.…”
Section: -Discussionmentioning
confidence: 99%
“…The vitrification process was done by adding one portion of the vitrification medium (Tris 2.4 gm + Citric Acid 1.4 g + Fructose 1.0 g + Streptomycin 5 µg + Penicillin 10 kIU is diluted in 100ml distilled Water with Soy lecithin at 1%(Andressa Dalmazzo et al, 2018) and 0.25 M sucrose) to one portion of fresh semen at 37 ˚C immediately after initial analysis (Pipan et al, 2020). After addition of vitrification media, vitrified semen was packed into straw straws (0.5 ml) are maintained at 5 °C for 30 min (equilibration time), then plunged directly into liquid N2 (LN2) for at least one week.…”
Section: Vitrification Media and Vitrification Processmentioning
confidence: 99%
“…Para avaliação da integridade física da membrana espermática, foi utilizado o corante supravital eosina/nigrosina (Minitube GmbH, Tiefenbach, Alemanha) (10) . A integridade funcional da membrana espermática foi avaliada através do teste hiposmótico.…”
Section: Avaliação Do Sêmenunclassified
“…Estas condições provocam a mudança do estado líquido para o estado amorfo da matéria, no qual o fluido que permanece no espaço intracelular adquire uma característica vítrea, impedindo a formação de cristais de gelo, e a ausência de estrutura atômica definida permite adequada dispersão da substância vítrea entre as organelas (6) . Esta técnica encontra-se bem estabelecida em humanos (7) , e experimentalmente apresenta bons resultados em jumentos (8) , equinos (9) , cães (10) e gatos (6) .…”
Section: Introductionunclassified
“…This last condition perhaps would be due to that monosaccharides are more easily metabolized by spermatozoa. Recently Zakošek Pipan et al [ 63 ] reported the effects of different sucrose and soy lecithin concentrations utilized to confront different vitrification techniques for canine semen cryopreservation. The results obtained showed that the vitrification media with soy lecithin and sucrose cause minimal wane in the quality of the dog seed after devitrification, as they keep unchanged physiological parameters of the sperm, such as morphology, vitality, total and progressive motility, acrosome, the integrity of the sperm tail membrane, and DNA.…”
Section: Introductionmentioning
confidence: 99%